1994
DOI: 10.1002/1097-0142(19940315)73:6<1589::aid-cncr2820730609>3.0.co;2-7
|View full text |Cite
|
Sign up to set email alerts
|

Detection of point mutations in the K-ras oncogene at codon 12 in pure pancreatic juice for diagnosis of pancreatic carcinoma

Abstract: Background. Mutations in the K‐ras oncogene at codon 12 are detected at a remarkably high frequency in pancreatic carcinomas and are believed to be a critical event in oncogenesis. The authors attempted to detect K‐ras mutations in DNA obtained from pure pancreatic juice collected endoscopically, as a novel diagnostic approach to pancreatic carcinoma. Methods. K‐ras mutations were examined using the two‐step polymerase chain reaction (PCR) combined with restriction enzyme digestion, followed by nonra‐dioisotop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
46
0
3

Year Published

1996
1996
2010
2010

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 133 publications
(49 citation statements)
references
References 18 publications
0
46
0
3
Order By: Relevance
“…K-ras point mutations at codon 12 have been identified in more than 90 % of patients with PAC [7]. Several studies have reported the detection of cells harboring K-ras mutations in pure pancreatic juice [8], in duodenal aspirates [9], and in pancreatic duct brushings [10] in patients with PAC. Moreover, K-ras mutation has been found in hyperplasic ductal lesions of the pancreas, which have been considered to be precursors of ductal adenocarcinoma in both animal studies [11] and human studies [12,13].…”
mentioning
confidence: 55%
“…K-ras point mutations at codon 12 have been identified in more than 90 % of patients with PAC [7]. Several studies have reported the detection of cells harboring K-ras mutations in pure pancreatic juice [8], in duodenal aspirates [9], and in pancreatic duct brushings [10] in patients with PAC. Moreover, K-ras mutation has been found in hyperplasic ductal lesions of the pancreas, which have been considered to be precursors of ductal adenocarcinoma in both animal studies [11] and human studies [12,13].…”
mentioning
confidence: 55%
“…To confirm the diagnosis of pancreatic carcinoma, various clinical samples were used, including needle biopsy specimens (Shibata et al, 1990), pancreatic juice (Kondo et al, 1994), duodenal fluid (Wilentz et al, 1998) and bile (Ajiki et al, 1995) from a choledochal drainage tube. However, the collection of sufficient samples for a molecular diagnosis is often difficult.…”
Section: Discussionmentioning
confidence: 99%
“…In 5 of 14 cases (35.7%) of biliary tract carcinomas, including bile duct and gallbladder carcinomas, K-ras mutation was detected in both the supernatants and cell clusters of cytologic smears of bile or pancreatic juice. The K-ras mutation detection rates of pancreas and biliary tract carcinomas obtained in the present study are within the previously reported ranges (50-100% in pancreas carcinoma [1][2][3][7][8][9][10][11][12][13]17,[26][27][28][29] ) and 29.0-56.5% in biliary tract carcinoma. [30][31][32][33] In several pancreatic adenocarcinomas, K-ras mutations were detected in bile as well as pancreatic juice.…”
Section: Discussionmentioning
confidence: 99%